Effectiveness of a manual dexterity training program to improve executive functioning in preschool children: an individual difference analysis - Stuhr, Christina; Hughes, Charmayne Mary Lee; Stöckel, Tino (Frontiers in Cognition, 2025)
IntroductionThe present study employed the Jacobson-Truax reliable change index (RCI) to examine the effectiveness of a 4-week manual dexterity training program embedded in a socially enriched group setting to improve working memory performance, cognitive functioning, and numeracy skills in preschool children.MethodsForty-five typically developing children aged between 5 and 6 years of age were randomly allocated to a 4-week intervention program (n = 20) or a control condition (n = 25). Pre- and post-test assessments were conducted using two manual dexterity measures, three working memory measures, as well as tasks evaluating inhibition, cognitive flexibility, processing speed, and numeracy skills.ResultsRelative to control participants, a greater number of participants in the intervention group showed statistically and clinically significant post-intervention gains in manual dexterity, working memory, and selective attention. However, the benefits of the intervention did not extend to response inhibition, cognitive flexibility, processing speed, and numeracy skills. Moreover, a greater percentage of children in the intervention group exhibited improvements in both manual dexterity and all working memory tasks than children in the control group.DiscussionOverall, findings from this study corroborate existing research demonstrating the positive effects of manual dexterity training on working memory performance and highlight the use of individual-level analysis to determine the effectiveness of cognitive-motor training and interventions.